APAKAH UKURAN PERUSAHAAN DAPAT MEMODERASI EFEK RETURN ON ASSET TERHADAP PRICE TO BOOK VALUE? - Jumsiani, Jumsiani; Kadir, Muh. Akob; Idris, Ma’ruf (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to test and analyze the influence of Company Size as a Moderating Variable Between Return On Asset (ROA) on Company Value (PBV) in Automotive and Component Companies on the Indonesia Stock Exchange. The type of research used is a quantitative approach, the population in this study is 16 Automotive and Component Companies on the Indonesia Stock Exchange, the sampling technique uses the saturated sample method with a sample number of 16 companies. The analysis used in hypothesis testing is a regression analysis of MRA panel data with the help of Eviews 13 Software. The results of the analysis provide evidence that Return on Asset (ROA) has a negative effect not significantly on Company Value (PBV), The size of the company can be proven to strengthen the relationship between Return on Asset and Company Value (PBV) . Keywords: Return on Asset (ROA), Firm Value, PBV, Firm Size